Peanut‐induced anaphylaxis in children and adolescents: Data from the European Anaphylaxis Registry. Issue 5 (3rd January 2021) - Maris, Ioana; Dölle‐Bierke, Sabine; Renaudin, Jean‐Marie; Lange, Lars; Koehli, Alice; Spindler, Thomas; Hourihane, Jonathan; Scherer, Kathrin; Nemat, Katja; Kemen, C.; Neustädter, Irena; Vogelberg, Christian; et al.
Abstract: Background: Peanut allergy has a rising prevalence in high‐income countries, affecting 0.5%–1.4% of children. This study aimed to better understand peanut anaphylaxis in comparison to anaphylaxis to other food triggers in European children and adolescents. Methods: Data was sourced from the European Anaphylaxis Registry via an online questionnaire, after in‐depth review of food‐induced anaphylaxis cases in a tertiary paediatric allergy centre. Results: 3514 cases of food anaphylaxis were reported between July 2007 ‐ March 2018, 56% in patients younger than 18 years. Peanut anaphylaxis was recorded in 459 children and adolescents (85% of all peanut anaphylaxis cases). Previous reactions (42% vs. 38%; p  = .001), asthma comorbidity (47% vs. 35%; p  < .001), relevant cofactors (29% vs. 22%; p  = .004) and biphasic reactions (10% vs. 4%; p  = .001) were more commonly reported in peanut anaphylaxis. Most cases were labelled as severe anaphylaxis (Ring&Messmer grade III 65% vs. 56% and grade IV 1.1% vs. 0.9%; p  = .001). Self‐administration of intramuscular adrenaline was low (17% vs. 15%), professional adrenaline administration was higher in non‐peanut food anaphylaxis (34% vs. 26%; p  = .003). Hospitalization was higher for peanut anaphylaxis (67% vs. 54%; p  = .004). Conclusions: The European Anaphylaxis Registry data confirmed peanut as one of the major causes of severe, potentially life‐threatening allergic reactions in European children, with some characteristic features e.g., presence of asthma comorbidity and increased rate of biphasic reactions. Usage of intramuscular adrenaline as first‐line treatment is low and needs to be improved. The Registry, designed as the largest database on anaphylaxis, allows continuous assessment of this condition. Abstract : The European Anaphylaxis Registry data confirmed peanut as one of the major causes of severe allergic reactions in European children. Asthma was a more common comorbidity in peanut allergic children. Peanut anaphylaxis was more likely to be elicited by smaller amounts, and presented with more severe symptoms. The frequency of biphasic reactions was higher compared to anaphylaxis triggered by other food. Abbreviations: FIA, food‐induced anaphylaxis; nP‐FA, non‐peanut‐induced food anaphylaxis; P‐FA, peanut‐induced food anaphylaxis